2004
DOI: 10.1111/j.1551-2916.2004.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Solution Formation in the Synthesis of Fe‐Zircon

Abstract: To investigate solid‐solution formation in the iron‐doped silicate (zircon) system, different samples were prepared by the ceramic method with addition of LiF as a mineralizer. The results of X‐ray powder diffraction (XRD), 57Fe Mössbauer, and UV–visible spectroscopy showed that in the as‐prepared samples, only a small fraction of iron, i.e., about 2.5 mol%, is hosted in the zircon structure as paramagnetic Fe3+ species, while the remaining Fe3+ cations form magnetic α‐Fe2O3 particles that are trapped in the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Conclusions reached in the literature concerning the actual location of dopant cations and their valence in the zircon lattice [15][16][17][18]22,23 lack consistency. During the synthesis of iron coral (a zircon based pigment) by coprecipitation routes, Llusar et al 3 observed that iron mainly appears to be in two different forms: (i) segregated, forming Fe 2 O 3 aggregates of different morphology and sizes or (ii) as micron sized Fe 2 O 3 particles adsorbed or encrusted on the surface of the bigger zirconia monoliths.…”
Section: Introductionmentioning
confidence: 88%
“…Conclusions reached in the literature concerning the actual location of dopant cations and their valence in the zircon lattice [15][16][17][18]22,23 lack consistency. During the synthesis of iron coral (a zircon based pigment) by coprecipitation routes, Llusar et al 3 observed that iron mainly appears to be in two different forms: (i) segregated, forming Fe 2 O 3 aggregates of different morphology and sizes or (ii) as micron sized Fe 2 O 3 particles adsorbed or encrusted on the surface of the bigger zirconia monoliths.…”
Section: Introductionmentioning
confidence: 88%
“…51,52 The reduction of network connectivity appears as a triggering event, since silicates feature partially covalent bonding and consequently limited ionic interdiffusion 53 ; moreover, zircon formation is associated to the motion of silicon and oxygen ions, rather than of zirconium ones. 54 The beneficial effect of TiO 2 was exploited also for mullite ceramics embedding ZrO 2 nano-particles, to form nano-structured zirconia-toughened composites. 35 As mentioned above, the approach of mixing preceramic polymers with nano-sized fillers for the synthesis of oxynitrides faces the intrinsic complexity in the phase assemblage within the ceramic residue, which is produced under non-oxidizing heating atmosphere.…”
Section: Reaction Paths and Mixture Reactivitymentioning
confidence: 99%
“…The obtained particulate product, with large particle size and very wide size distribution, does not meet the requirement of some applications such as high temperature ink. Usually, mineralizers [8], such as NaF and LiF, are added into the precursor mixture to lower the reaction temperature to around 1000°C. However, mineralizer can induce serious aggregation of the particles, and lead to the formation of impurity through the reaction with reactants.…”
Section: Introductionmentioning
confidence: 99%